Impact of strategic leadership on strategic competitive advantage through strategic thinking and strategic planning: A bi-meditational research - Mohammad Hunitie (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Confusion between strategic planning and strategic thinking in the context of strategic leadership and its effect on competitive advantage was the foremost rationale for this study to come into view. Thereby, the aim of this study was to examine the role of two mediating variables, i.e., strategic planning and strategic thinking in the impact of strategic leadership on competitive advantage. Scoping health care sector in Jordan resulted in three public hospitals agreed to participate in the study. Data were gathered using a questionnaire developed on the basis of literature review. A total of 1000 questionnaires were administered to hospitals. A total 521 questionnaires were returned with a response rate of 52.1%. The results pinpointed that strategic leadership significantly predicted strategic planning, strategic thinking and competitive advantage. the results also revealed that strategic planning and strategic thinking significantly and positively related to competitive advantage. accordingly, it was approved that strategic planning and strategic thinking mediated the effect of strategic leadership on competitive advantage. Despite that the influence of strategic thinking on competitive advantage was greater than the influence of strategic planning on competitive advantage. The study hold the perspective that both strategic planning and strategic thinking were essential in the context of strategic leadership, since strategies are developed by strategic thinking and operationalized via strategic planning.
Keywords: M10; 650; strategic leadership; strategic thinking; strategic planning; competitive advantage